2016
DOI: 10.1371/journal.pone.0151847
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Stressor Differential Tolerances: Possible Implications at the Population Level

Abstract: The probability of the most sensitive genotypes being eliminated from a population due to a contaminant pulse–genetic erosion–is negatively associated to the within-genotype variation. A sensitive genotype with a small phenotypic variation would be more prone to be lost–a critically sensitive genotype. Furthermore, natural populations inhabiting contaminated sites are usually exposed to several pollutants. Such co- or sequential exposure can have severe effects if at least some tolerant clonal lineages survivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Mitigation strategies to reduce the impact of environmental change are limited because the effect of multiple stressors can be synergistic (greater than the sum of individual effects), antagonistic (resulting from the contrasting action of two or more stressors) or additive (sum of the individual effects) 7 , making predictions of the impact of multiple stressors compared to a single stressor challenging 8 , 9 . Furthermore, population level responses can vary dramatically because of differences in environmental sensitivity 10 , tolerance among individuals 11 , ecological trade-offs and patterns of local adaptation 12 , 13 . Modelling efforts have demonstrated that some of the main drivers of global change (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Mitigation strategies to reduce the impact of environmental change are limited because the effect of multiple stressors can be synergistic (greater than the sum of individual effects), antagonistic (resulting from the contrasting action of two or more stressors) or additive (sum of the individual effects) 7 , making predictions of the impact of multiple stressors compared to a single stressor challenging 8 , 9 . Furthermore, population level responses can vary dramatically because of differences in environmental sensitivity 10 , tolerance among individuals 11 , ecological trade-offs and patterns of local adaptation 12 , 13 . Modelling efforts have demonstrated that some of the main drivers of global change (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Greater metal tolerance of these two species together with elimination of competing species, that were probably metal sensitive, had possibly led to a very large increase in their populations. Concurrent tolerance of S. opolinensis and C. bioculatum to Cu and Zn may have resulted through multiple tolerance or co-tolerance (Venâncio et al 2016), but which one of the two was operating in these two organisms is di cult to pin point. Laboratory experiments in future can only throw light on the mode of concurrent tolerance to test metals in the present study.…”
Section: Discussionmentioning
confidence: 99%